2015
DOI: 10.1016/j.jes.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

A screening assay for thyroid hormone signaling disruption based on thyroid hormone-response gene expression analysis in the frog Pelophylax nigromaculatus

Abstract: Amphibian metamorphosis provides a wonderful model to study the thyroid hormone (TH) signaling disrupting activity of environmental chemicals, with Xenopus laevis as the most commonly used species. This study aimed to establish a rapid and sensitive screening assay based on TH-response gene expression analysis using Pelophylax nigromaculatus, a native frog species distributed widely in East Asia, especially in China. To achieve this, five candidate TH-response genes that were sensitive to T3 induction were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
0
3
1
Order By: Relevance
“…In our study, it is possible that the slow development rate due to predation pressure is due to the relatively long tadpole period of this species. The metamorphosis timing of juvenile frogs in our study was especially slower, at around 100 to 120 days when compared to the 48 to 75 days that was evidenced in previous studies [ 57 , 58 , 59 , 60 ] that analyzed the same species. This may be due to the protein content of the food, or the laboratory temperature conditions, but such an explanation cannot be accurately confirmed from the papers of studies on the same species.…”
Section: Discussioncontrasting
confidence: 48%
“…In our study, it is possible that the slow development rate due to predation pressure is due to the relatively long tadpole period of this species. The metamorphosis timing of juvenile frogs in our study was especially slower, at around 100 to 120 days when compared to the 48 to 75 days that was evidenced in previous studies [ 57 , 58 , 59 , 60 ] that analyzed the same species. This may be due to the protein content of the food, or the laboratory temperature conditions, but such an explanation cannot be accurately confirmed from the papers of studies on the same species.…”
Section: Discussioncontrasting
confidence: 48%
“…Molecular analysis of Pelophylax (P.) nigromaculatus intestines showed that tadpoles exposed to low concentrations of TBBPA (1 nM) had agonistic effects on T 3 -induced expression of TH-response genes (Table 3). In contrast, higher TBBPA concentrations (100–1,000 nM) had antagonistic effects in the same experimental paradigm (74). The molecular mechanisms by which TBBPA may act as both an agonist and antagonist of tissue-specific development while endogenous TH levels vary need to be ascertained.…”
Section: Industrial and Agricultural Chemicalsmentioning
confidence: 89%
“…However, during metamorphic climax when TH amounts are maximal, developmental stage transitions were delayed (80). An additional potential confounder may be the amount of TBBPA that metamorphic anurans are exposed to (74). Molecular analysis of Pelophylax (P.) nigromaculatus intestines showed that tadpoles exposed to low concentrations of TBBPA (1 nM) had agonistic effects on T 3 -induced expression of TH-response genes (Table 3).…”
Section: Industrial and Agricultural Chemicalsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figure S1: Putative AMP filters used for amphibians and insects; Figure S2: Runtime and memory of each dataset through rAMPage; Figure S3: Score, length, and charge distribution of filtered putative AMPs; Figure S4: Amino acid composition of filtered putative AMPs; Figure S5: Antimicrobial susceptibility and hemolysis testing of 21 putative AMPs; Figure S6: Multiple sequence alignments of moderately to highly active AMPs; Figure S7: Multiple sequence alignments of moderately to highly active AMP precursors; Figure S8: Distribution of alignment of filtered putative AMPs to mature reference AMPs; Figure S9: Distribution of reference mature AMPs; Figure S10: Approach for peptides with multiple cleavage sites; Table S1: Peptide naming convention; Table S2: Subset of 21 putative AMPs synthesized and validated against E. coli and S. aureus; Table S3: Annotation of moderately to highly active putative mature AMPs; Table S4: Major options for rAMPage; Table S5: Sensitivity of all putative AMP filter combinations; Table S6: Amphibian RNA-seq datasets; Table S7: Insect RNA-seq datasets; Table S8: Breakdown of AMP sequences in AMP databases; Table S9: Shell scripting dependencies of rAMPage; Table S10: Bioinformatic tool dependencies of rAMPage; Table S11: Command and parameters for each step of rAMPage. References [ 11 , 27 , 29 , 30 , 41 , 59 , 60 , 61 , 62 , 63 , 64 , 73 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ...…”
mentioning
confidence: 99%